UMP signs MoU with IIM on Governance, Ethics and Integrity - Irene, Wei Kiong Ting (2018)
Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with The Malaysian Institute of Integrity (IIM) on 6th August 2018 to improve corporate governance systems, ethics and integrity in the pursuit of establishing a morally-sound and ethical society.